HUBUNGAN TINGKAT DEPRESI DENGAN KUALITAS HIDUP PERAWAT RSUD PROF. DR. W Z JOHANNES DI ERA PANDEMI COVID-19 - Matulessy, Giovanni Kathlix immanuel; Buntoro, Ika Febianti; Etty Dedy, Maria Agnes (Universitas Nusa Cendana, 2023)
Background: The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has caused an outbreak of Coronavirus Disease (COVID19) which affects various fields in the world, one of which is the health sector. Nurses are one group of health workers who have the largest proportion of the number with a high level of work intensity in the hospital. High levels of work intensity, difficulty establishing relationships with family members, difficulties in caring for critical patients, risk of infection, and other factors can cause psychological disorders such as depression for nurses. Depression in nurses will have an impact on emotional, cognitive, motivational changes, feelings of anxiety, restlessness, feelings of deterioration which can reduce work effectiveness and can affect the quality of life of the nurses themselves. Poor quality of life has an important role for welfare in living life and will affect health problems that may arise in the future Objective: To determine the relationship between the level of depression and the quality of life of nurses during the COVID-19 pandemic era at Prof. Dr. W. Z. Johannes Kupang Methods: This research is an observational analytic study with a cross sectional design conducted on nurses in the NICU, ICU and Komodo rooms at Prof. Dr. W. Z. Johannes Kupang, by filling in the Beck Depression Inventory II (BDI-II) questionnaire. and The World Health Organization Quaity Of Life (WHOQOL) –BREF questionnaire. The sampling technique used total sampling with 44 respondents who met the inclusion and exclusion criteria. The study was analyzed by univariate, bivariate using the chi-square test. Results: From 44 respondents, it was found that 29 respondents (65.9%) had no depression, 12 respondents (27.27%) had mild depression and 3 respondents (6.8%) had moderate depression. From 44 respondents also found 30 respondents (68.18%) had a bad quality of life and 14 respondents (31.18%) had a good quality of life. The results of the bivariate analysis test in this study obtained p = 0.035 (p <0.05). Conclusion: There is a significant relationship between the level of depression and the quality of life of nurses during the COVID-19 pandemic era at Prof. Dr. W. Z. Johannes Kupang.